Fungal peritonitis among the peritoneal dialysis patients of four Turkish centres - (:unkn) unknown (My University, 2010)
This study evaluates the clinical findings and treatment of continuous ambulatory peritoneal dialysis (CAPD) patients with fungal peritonitis in Istanbul from 2000 to 2010. The clinical records of 15 patients with fungal peritonitis among the total 795 patients were reviewed for the clinical and laboratory data. The mean duration of dialysis from the initiation of treatment until the development of fungal peritonitis was 41.14 months. Fungal peritonitis was the primary episode of infection in eight patients. In five other patients previous intensive antibiotherapy was documented. The isolated mircoboes were Candida albicans in six, non-C. albicans in eight and Aspergillus fumigatus in one patient. Tenckoff catheters were removed in all cases and antifungal treatment was given for a minimum of three weeks. Two patients died in the hospital due to the fungal infection whereas others were transferred to haemodialysis.This study highlights the importance of removing the catheter and initiating antifungal therapy as soon as possible in cases of fungal peritonitis because it is responsible for high morbidity and mortality. © 2010 European Dialysis and Transplant Nurses Association/European Renal Care Association.
Keywords: Candida species; CAPD; Fungal peritonitis; Morbidity; Mortality